Legotastic / Ahmad Syahmi Isa - Isa, Ahmad Syahmi (2021)
Legotastic was established in April 2021,which provides all Star Wars toys and hobbies for all local Star Wars fans.All the products are in lego form which requires one to assemble every part to complete the build. Legotastic target markets in terms of demographic are not just for kids but also towards adults and teenagers regardless of their gender.This is because Star Wars Saga has been going on since 1977 which is almost 4 decades.That explains why their fanbase consists of people of all ages.The trend of making dioramas or display collection are fulfilled by us as we sell almost all the Star Wars figure ever produced. Legotastic also believes that it is our responsibility to provide to the fans what they want as now they don’t have to buy from international e-commerce sites like ebay and amazon where they can just walk into our store and grab their favorite Star Wars sets.